Persepsi Mahasiswa STAIN Curup Tentang Pendapat prof. Dr. Quraish Shihab dalam Tafsir al-Misbah bahwa Perempuan Tidak Wajib Memakai Jilbab - Rafia Arcanita (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This research try to answer on how students’ comprehension on surah An- Nur verse 31 and surah Al Ahzab verse 59 based on Al – misbah commentation. Women no need to wear hijab, in contrast to the academic role, according to the students’ contract, they have to wear hijab. After conducting the research discovered two perception First, there are some students who disagree with that especially the students with islamic education backgound (Islamic Dormitiry School and MA). Second, some of them agree especially the students from the general educational background (Senior high school and Vocational School).